Range-wide declines of northern spotted owl populations in the Pacific Northwest: A meta-analysis. (July 2021) - Franklin, Alan B.; Dugger, Katie M.; Lesmeister, Damon B.; Davis, Raymond J.; Wiens, J. David; White, Gary C.; Nichols, James D.; Hines, James E.; Yackulic, Charles B.; Schwarz, Carl J.; Ackers, Steven H.; Andrews, L. Steven; et al.
Abstract: The northern spotted owl ( Strix occidentalis caurina ) inhabits older coniferous forests in the Pacific Northwest and has been at the center of forest management issues in this region. The immediate threats to this federally listed species include habitat loss and competition with barred owls ( Strix varia ), which invaded from eastern North America. We conducted a prospective meta-analysis to assess population trends and factors affecting those trends in northern spotted owls using 26 years of survey and capture-recapture data from 11 study areas across the owls' geographic range to analyze demographic traits, rates of population change, and occupancy parameters for spotted owl territories. We found that northern spotted owl populations experienced significant declines of 6–9% annually on 6 study areas and 2–5% annually on 5 other study areas. Annual declines translated to ≤35% of the populations remaining on 7 study areas since 1995. Barred owl presence on spotted owl territories was the primary factor negatively affecting apparent survival, recruitment, and ultimately, rates of population change. Analysis of spotted and barred owl detections in an occupancy framework corroborated the capture-recapture analyses with barred owl presence increasing territorial extinction and decreasing territorial colonization of spotted owls. While landscape habitat components reduced the effect of barred owls on these rates of decline, they did not reverse the negative trend. Our analyses indicated that northern spotted owl populations potentially face extirpation if the negative effects of barred owls are not ameliorated while maintaining northern spotted owl habitat across their range. Highlights: A meta-analysis assessed population trends in northern spotted owls (NSO) using 26 years of data from 11 study areas NSO populations declined by 6–9% annually (6 study areas) and 2-5% annually (5 study areas) ≤35% of NSO populations remained on 7 study areas since 1995 Barred owls (BO) were the primary factor negatively affecting NSO life history traits and rates of population change NSO populations potentially face extirpation if the negative effects of BOs are not ameliorated while maintaining NSO habitat